2015
DOI: 10.1039/c5ta03686k
|View full text |Cite
|
Sign up to set email alerts
|

Identifying the optimum thickness of electron transport layers for highly efficient perovskite planar solar cells

Abstract: The fabrication of pinhole-free and compact electron transport layer is crucial for achieving high power conversion efficiency of perovskite solar cells. In this work, we report efficient perovskite solar cells using ultrathin TiO 2 films (5-20 nm) as high-quality electron transport layers deposited by atomic layer deposition technique.The as-prepared solar cells on FTO substrates show a high efficiency of 13.6% employing the optimum 10 nm TiO 2 layer thickness. Furthermore, the flexible cells on PET substrate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
50
0
1

Year Published

2016
2016
2020
2020

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 100 publications
(54 citation statements)
references
References 38 publications
3
50
0
1
Order By: Relevance
“…Regarding polymer based cells, in this study we have surpassed the reported power conversion efficiency (PCE) record for PCPDTBT acting as HTM 20 , while for P3HT and PTB7, the efficiencies obtained are similar to the best efficiencies reported avoiding the use of dopants 31, 32 .…”
Section: Resultssupporting
confidence: 47%
“…Regarding polymer based cells, in this study we have surpassed the reported power conversion efficiency (PCE) record for PCPDTBT acting as HTM 20 , while for P3HT and PTB7, the efficiencies obtained are similar to the best efficiencies reported avoiding the use of dopants 31, 32 .…”
Section: Resultssupporting
confidence: 47%
“…There were several attempts in the application of real dopant-free homopolymer as HTMs. [107] At the same time, the classic conductive polymer ink poly(3,4-ethylene dioxythiophene):poly(styrene sulfonic acid) (PEDOT:PSS) played a leading role in the construction of a p-i-n type planar perovskite solar cell. Recently, using pristine P3HT-based HTM, a PCE of 13.6% was achieved in a device structure of glass/FTO/ALD-TiO 2 /CH 3 NH 3 PbI 3−x Cl x /P3HT/ Ag.…”
Section: Polymers Materialsmentioning
confidence: 99%
“…This parameter could affect the performance of PEC cells as thick film will increase the series resistance which can reduce the current and in some cases, increase charge recombination rate. Meanwhile, thin layer of photoanode not only reduce light absorption which subsequently reduce the number of exciton generation, but also lead to incomplete surface coverage and pinholes formation which increases the possibility of charge carrier recombination . Hence, the right thickness of photoanode is necessary to ensure high photocatalytic activity in solar water splitting.…”
Section: Introductionmentioning
confidence: 99%